Theorising Justice A Primer for Social Scientists - Ohlsson, Johanna; Przybylinski, Stephen (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND license. Bringing together divergent approaches to justice theorising, this volume connects normative and philosophical theories with the more empirically focused approaches emerging today in the social and political sciences and policy scholarship. The chapters overview a variety of mainstream approaches and radical critiques of justice to illustrate their value in addressing the pressing problems of climate change and economic development. Stressing the value of assessing justice theories in light of the material conditions of our changing world, the book concludes with an in-depth synthesis of how these wide ranging approaches to justice will be useful for students, scholars and practitioners concerned with realising justice.